Claudius Galen, researcher of the circulatory system - Morales, Melody G.; Mendoza, Jarod B.; Sancan, Ariot (Revista Gregoriana de Ciencias de la Salud, 2024)
The human body contains numerous mysteries that have been explored throughout its evolution. Their systems work together to maintain homeostasis and harmony, with the circulatory system being a topic of great interest since ancient times, especially for researchers like Galen. The objective of this work was to describe Galen's discoveries about the circulatory system and its relevance in current medicine. Through a detailed literature search, it was found that Galen introduced ideas that were extremely advanced for his time. The continuous evolution of the study of the cardiovascular system over time has been fundamental, allowing progress in the understanding and treatment of various diseases related to this system.